Neuromuscular Rehabilitation in the Prevention of Anterior Cruciate Ligament Injury in Children and Adolescents - Câmara, Manuel Pina; Pinheiro, MD, PhD, João Páscoa; Figueiredo, MD, PhD, Pedro; Branco, MD, PhD, João Paulo (International Journal of Innovative Research in Medical Science, 2025)
Introduction: Knee injuries are increasingly common in the pediatric population, with anterior cruciate ligament (ACL) ruptures standing out due to their rising incidence in children and adolescents. These injuries are associated with significant clinical and functional consequences, such as the need for surgical intervention, lengthy rehabilitation, low return-to-sport rates, high re-injury risk, and early-onset osteoarthritis. They may also impact school performance. This study aims to evaluate the effectiveness of neuromuscular training (NMT) programs in preventing ACL injuries in young populations and to identify the most effective protocols, components, and contributing factors. Methods: A systematic review was conducted following PRISMA guidelines using PubMed, Embase, and Web of Science, covering studies from 2014 to 2024. The selection followed the PICO framework, focusing on individuals under 18 years old receiving neuromuscular or proprioceptive training, compared to control groups or studies analyzing biomechanical risk factors. Only peer-reviewed articles in English or Portuguese were included. Two independent reviewers screened studies, extracted data, and assessed quality. Outcomes evaluated were ACL injury incidence and biomechanical risk factors. Results: Of the 64 initially identified articles, 9 met the inclusion criteria3 systematic reviews and 6 original studies. The systematic reviews highlighted significant reductions in ACL injury rates and emphasized the influence of sport type and external factors. The original studies reported improvements in neuromuscular and biomechanical control following NMT protocols. Conclusions: NMT was shown to be effective, particularly when introduced early in youth. Key factors for successful implementation include exercise variety, sensory feedback, and professional supervision. Additionally, unstructured play may contribute to natural protective adaptations. Future research should refine and personalize preventive strategies.